Efficacy of Transcranial Direct-Current Stimulation in Catatonia: A Review and Case Series - Haroche, Alexandre; Giraud, Nolwenn; Vinckier, Fabien; Amad, Ali; Rogers, Jonathan; Moyal, Mylène; Canivet, Laetitia; Berkovitch, Lucie; Gaillard, Raphaël; Attali, David; Plaze, Marion (Frontiers in Psychiatry, 2022)
Catatonia is a severe neuropsychiatric syndrome, usually treated by benzodiazepines and electroconvulsive therapy. However, therapeutic alternatives are limited, which is particularly critical in situations of treatment resistance or when electroconvulsive therapy is not available. Transcranial direct-current stimulation (tDCS) is a promising non-invasive neuromodulatory technique that has shown efficacy in other psychiatric conditions. We present the largest case series of tDCS use in catatonia, consisting of eight patients in whom tDCS targeting the left dorsolateral prefrontal cortex and temporoparietal junction was employed. We used a General Linear Mixed Model to isolate the effect of tDCS from other confounding factors such as time (spontaneous evolution) or co-prescriptions. The results indicate that tDCS seems to be effective in reducing catatonic symptoms in addition to symptomatic pharmacotherapies such as lorazepam. These results corroborate a synthesis of five previous case reports of catatonia treated by tDCS in the literature. However, the specific efficacy of tDCS in catatonia remains to be demonstrated in a randomised controlled trial. The development of therapeutic alternatives in catatonia is of paramount importance.